Evaluation of Yield and Pigment Content of Eleven Genotypes of Green and Purple Pod Yard Long Bean (Vigna unguiculata (L.) Walp.) - Sari Dewi, Okky Tiara; Syukur, Muhamad (Journal of Tropical Crop Science, 2019)
The consumption of yard long bean in Indonesia is high and it has been increasing continuously, but the production and harvest area has been decreasing. New, superior long bean varieties with higher productivity are required to meet the increasing demands. The aim of this study was to evaluate the morphological and yield characters of selected purple and green long bean genotypes. The research was conducted from February to May 2018 in the Madiun district, East Java, Indonesia. The experiment was laid out in a randomized complete block design with genotypes as the single factor treatment, replicated three times. Eleven yard long bean genotypes were tested, consisting of four new genotypes, F7-013014- 4U-16-1-1, “F7-013014-4U-16-1-2”, “F7-013014- 4U-16-1-3”, and “F7-013014-7P-4-1-1”, and seven control genotypes, “KP13”, “KP14”, “KP Putih China”, “KP Putih China”, “Borneo”, “Sabrina” and “Parade”. The new genotypes, “F7-013014-4U-16-1-1, “F7- 013014-4U-16-1-2”, “F7-013014-4U-16-1-3”, and “F7-013014-7P-4-1-1” had at least one superior characters compared to the control genotypes, i.e. earlier fl owering and time to harvest, longer leaves, greater pod weight, longer pods, larger pod diameter, and higher contents of anthocyanin, carotene, chlorophyll a, chlorophyll b, and total chlorophyll. Keywords: anthocyanin, genotype, pigment, carotene, chlorophyll